An RNN-Based Algorithm for Decentralized-Partial-Consensus Constrained Optimization - Xia, Zicong; Liu, Yang; Qiu, Jianlong; Ruan, Qihua; Cao, Jinde (IEEE transaction on neural networks and learning systems, 2023)
This technical note proposes a decentralized-partial-consensus optimization (DPCO) problem with inequality constraints. The partial-consensus matrix originating from the Laplacian matrix is constructed to tackle the partial-consensus constraints. A continuous-time algorithm based on multiple interconnected recurrent neural networks (RNNs) is derived to solve the optimization problem. In addition, based on nonsmooth analysis and Lyapunov theory, the convergence of continuous-time algorithm is further proved. Finally, several examples demonstrate the effectiveness of main results.